Critical analysis of the role of the school management teams in enhancing the quality of teaching and learning in selected schools in Ellisras circuit - Mononyane, Mmamoele Josephine (Central University of Technology, 2022)
Globally, school leaders and managers are pressured to show their contribution towards achieving the educational outcomes prioritised by an educational system. As a management structure, the School Management Team is ultimately responsible and accountable for the results of the learners. Previous studies have shown that school leadership is second only to teaching when it comes to the achievement of the learners. The purpose of this qualitative study was to explain and analyse how the different Principals, Deputy Principals, and Departmental Heads perceive, experience, and perform their leadership roles in selected schools in Ellisras Circuit. Furthermore, the researcher investigated their ability to function as a team, and how the role affects the culture of teaching and learning. The 12 SMT members that were purposely sampled are directly involved in leading and managing schools. Data on the role of the SMT was collected by relevant documents, semi-structured interviews, and observation of leadership practices of at least three participants. Themes and subthemes such as role knowledge and understanding, teamwork, leadership theories, and leadership preparation were identified. The study found that role ambiguity was strong among the Deputy Principals and Departmental Heads. Furthermore, induction and mentorship of the SMT was insufficient, which directly impacted their performance in the role. There is no concrete evidence to show that teamwork is actively being promoted within the SMT or the school. The study found that SMT members were not aware of DL, but were aware of the instructional and transformational leadership perspectives. The study confirmed that there is a relationship between the quality of leadership and the quality of teaching and learning. The lack of time limited the pursuit of deeper insight on the role played by the SMT. This study recommends that the Circuit Office develop a mentorship and induction programme for newly appointed SMT members. Given their critical roles, the professional development of the Deputy Principals and Departmental Heads must be prioritised. Furthermore, it is recommended that an SMT should subscribe to at least two theories that inform its leadership practices. In a dynamic environment, school leadership should be aligned to educational reforms, community development, and technology.
Thesis (Master: Education: Education Leadership and Management)--Central University of Technology
Keywords: Role; Leadership practices; Educational outcomes; Teamwork; DL